IMPLEMENTASI BOOTSTRAP ADMINLTE PADA SISTEM INFORMASI PERHITUNGAN SETORAN HARIAN - Dadi Rosadi; Rinawati Rinawati (STMIK Mardira Indonesia, Bandung, 2019)
With the development of information technology which increasingly every day, indirectly requires every company to be able to make improvements and increase the effectiveness in performance by utilizing reliable human resources and technology information system that is appropriate and effective. The information required must be accurate and reliable so as to provide more value to the user of the information. Through this research, a web-based daily deposit calculation information system will be designed at the Holis 34.402.48 Bandung gas station that is implemented with Bootstrap Admin LTE which has features that can facilitate the admin in his work.. Through this research will be designed a web-based daily accounting information calculation system at Holis 34,402.48 Bandung Bus stations that have features that can facilitate the admin in his work. The design of this information system is done by using object-oriented methodology, which consists of Use Case Diagram, Use Case Scenario, Activity Diagram (Work Flow), Class Diagram, Sequence Diagram. The resulting application design has functions to perform processing, transaction processing, and generate reports. With a well-computerized information system, information is processed more quickly and calculations can be performed more precisely and accurately. Keyword : system, information, deposit, daily, web, responsive webDOI : http://doi.org/10.5281/zenodo.3631043